2003
DOI: 10.1155/edr.2003.183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gymnema montanum Leaves on Serum and Tissue Lipids in Alloxan Diabetic Rats

Abstract: The effect of Gymnema montanum leaves on alloxaninduced hyperlipidemia was studied in male Wistar rats. Ethanolic extract of G. montanum leaves was administered orally and different doses of the extract on blood glucose, serum and tissue lipids, hexokinase, glucose-6-phosphatase, thiobarbituric acid-reactive substances (TBARS), hydroperoxides, and glutathione in alloxan-induced diabetic rats were studied. G. montanum leaf extract (GLEt) at doses of 50, 100, 200 mg/kg body weight for 3 weeks suppressed the elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…This study for the first time confirms that the ethanol extract of H. angustifolia root has antidiabetic effects by stimulating glucose uptake in HepG2 cells, C2C12 myotubes, and 3T3-L1 adipocytes. Hypertriglyceridaemia and hypercholesterolaemia have been reported to be the primary factors of diabetic state involving in the development of atherosclerosis and coronary heart disease which are the secondary complications of diabetes (Ananthan et al 2003). Results from this study indicate that the extract administration could significantly reduce TG and TC levels while significantly increase HDL-C level in the STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 59%
“…This study for the first time confirms that the ethanol extract of H. angustifolia root has antidiabetic effects by stimulating glucose uptake in HepG2 cells, C2C12 myotubes, and 3T3-L1 adipocytes. Hypertriglyceridaemia and hypercholesterolaemia have been reported to be the primary factors of diabetic state involving in the development of atherosclerosis and coronary heart disease which are the secondary complications of diabetes (Ananthan et al 2003). Results from this study indicate that the extract administration could significantly reduce TG and TC levels while significantly increase HDL-C level in the STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, insulin reduces elevated cholesterol by different mechanisms, such as; increasing uptake of fatty acids into peripheral tissue and inhibiting lipolysis. In case of insulin resistance circumstances, lipolysis is not inhibited and leads to hyperlipidemia (Ananthan et al, 2003). These results showed that F. drudeana (400 mg kgG 1 ) and F. huber-morathii (200 and 400 mg kgG 1 ) medication brought back the increased levels of TG, TC and LDL-C of STZ-diabetic rats near to their normal levels.…”
Section: Discussionmentioning
confidence: 81%
“…Presence of hypertriglyceridemia and hypercholesterolemia and reduction of HDL-C are the most common lipid abnormalities that were reported in diabetic condition (Uttra et al, 2011). Under normal condition, TG is being hydrolyzed by lipoprotein lipase which was activated by insulin (Ananthan et al, 2003). Moreover, insulin reduces elevated cholesterol by different mechanisms, such as; increasing uptake of fatty acids into peripheral tissue and inhibiting lipolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic rats exhibited abnormalities in lipid metabolism as evidenced by the elevated levels of cholesterol, triglycerides, low-density lipoprotein cholesterol and very low-density lipoprotein cholesterol and low levels of HDL-C in group II. 38,39 Treatment with Berberis asiatica plant extract and standard drug reduced the elevated levels of TC, TG, LDL-C and LDL-C, whereas it showed the improvement in the level of HDL-C.…”
Section: Discussionmentioning
confidence: 99%